THE PROBLEM OF ASSESSING THE BAKING QUALITY OF WHEAT WITH GENETICALLY DIFFERENT ALLELES OF STORAGE PROTEINS - I. Toporash; M. Chervonis; O. Voloshenko (Zernovì Produkti ì Kombìkorma, 2023)
The article is devoted to the study of the wheat samples of the 3rd classwith the same quality indicators according to DSTU 3768, but had different baking properties. In particular, the “strength” of flour (W) significantly differed. The quantitative and qualitative state of the gluten-protein complex is significant factor for obtaining grain and flour of high baking quality. But only the quality indicators of red winter wheat according to DSTU 3768 - protein content, amount and quality of gluten cannot objectively characterize the baking quality of a specific batch of grain. For the main indications of the Ukrainian standard for wheat, all batches of wheat are practically identical. Foreign buyers do not use our Ukrainian standards, they give precedence to international methods and one of the most integral of them is the “strength” (W). The method demonstrates the main characteristics of the physical properties of wheat dough, which maybe especially important during bread making: elasticity (P), extensibility (L) and alveogram configuration coefficient (P/L). It has been established that the reason is the difference in the genetically determined alleles of the storage proteins of the studied samples. In the last years "filler" and "weak" varieties of wheat of domestic and foreign selection have appeared in Ukraine. In the conditions of replacing traditionally grown varieties of "strong" wheat in Ukraine with new high-yielding varieties of domestic and foreign breeding, it is not enough to determine the parameters recorded in DSTU 3768 to determine the baking quality, it is necessary to introduce new, more objective research methods. It is concluded that for an objective assessment of the baking properties of wheat, international standards ISO 27971, ISO 21415, ISO 5529 should be used.